Developing Nutritious Snack Menu from Vegetable and Fruits for the Pre-School in Klong Luang Child Development Center 7, Klong Luang District, Pathumthani Province - นวลจันทร์คง จุฑาวรรณ; สังข์วรรณะ สุจาริณี; มานะกล้า ศกุนตาล์; เจริญนนท์ ปัทมาภรณ์ (Journal of Health Science of Thailand, 2021)
This research was aimed at developing nutritious snack menu from vegetable and fruits (VF) based on their nutrient requirements and sensory evaluation in pre-school children of Klong Luang Child Development Center 7, Klong Luang District, Pathumthani Province. Forty three pre-school children aged 2-5 year old were purposively selected for VF consumption data provided by parent or care givers and 15 of them were selected through accidental sampling for sensory evaluation including taste, color, texture and overall acceptance using 3-point hedonic scale instrument for children with amount of intake 8 nutritious snack menu for 4 weeks. The results shown that preschoolers prefers vegetable to fruit. Their favorites VF were carrot, cucumber, pumpkin, orange, banana and ripe mango. The researchers developed snack based on behaviors of VF and snack consumption. A list of 8 menus including 6 desserts and 2 beverages prepared from VF were prepared as snacks for used in a week in the Child Development Center. The average energy of snack from VF was 102.50±26.20 kcal (less than 10% of energy requirement). The average of nutrient had high levels were protein (2.50 g), fiber (1.40 g) and Vitamin C (10.50 mg) in the snack. The pre-school children had highest preference of pumpkin pies in the sensory evaluation. Therefore, the development of a nutritious snack menu from VF should become a choice for promoting indirect VF intakes in preschoolers.